Respuesta :
To expand you must first distribute (multiply) the 2 to the numbers inside the parentheses
2(x - 5)
(2 * x) + (2 * (-5) )
2x + (-10)
2x - 10
There are no like terms, therefore (x - 5)2 expanded is 2x - 10
Hope this helped!
~ Just a girl in love with Shawn Mendes
Answer:
x2−10x+25
Step-by-step explanation:
Notice that this expression has the following special form:
(a+b)(a+b)=(a+b)^2(a+b)(a+b)=(a+b)
2
left parenthesis, a, plus, b, right parenthesis, left parenthesis, a, plus, b, right parenthesis, equals, left parenthesis, a, plus, b, right parenthesis, squared
This form is what we call "a perfect square":
(\blueD a+\maroonC b)^2=\blueD a^2+2\blueD a\maroonC b+\maroonC b^2(a+b)
2
=a
2
+2ab+b
2
left parenthesis, start color #11accd, a, end color #11accd, plus, start color #ed5fa6, b, end color #ed5fa6, right parenthesis, squared, equals, start color #11accd, a, end color #11accd, squared, plus, 2, start color #11accd, a, end color #11accd, start color #ed5fa6, b, end color #ed5fa6, plus, start color #ed5fa6, b, end color #ed5fa6, squared
Hint #22 / 2
\begin{aligned} &\phantom{=}(x-5)^2 \\\\ &=\big(\blueD x+(\maroonC{-5})\big)^2 \\\\ &=\blueD x^2+2(\blueD x)(\maroonC{-5})+(\maroonC{-5})^2 \\\\ &=x^2-10x+25 \end{aligned}
=(x−5)
2
=(x+(−5))
2
=x
2
+2(x)(−5)+(−5)
2
=x ^2 −10x+25